The development of vehicle stability control at Ford - Tseng, H.E.; Ashrafi, B.; Madau, D.; Allen Brown, T.; Recker, D. (IEEE/ASME transactions on mechatronics, 1999)
Addresses realistic subjects encountered in the challenge of achieving technology improvement in a vehicle stability control system. They include driver intent recognition, vehicle status measurement and estimation, control target generation, system actuation efficiency and smoothness, road bank angle detection, system development and evaluation, and fault detection.